Research on Thermal Field Dynamic Response in Air- conditioning Room during Start- Up Process - 张欢; 宋国军; 王志刚; 李瑞新; 李秋生 (Zhileng xuebao)
In this study, Fluent as a computational fluid dynamic software was used to simulate the process of unsteady heat conduction and convection of the air in an air - conditioning room during the start - up process of the air - conditioning instruments. On the basis of the flying- rising curves obtained from the process of the simulation, a mathematics model established to reflect the dynamic response of the air in the air - conditioning room during the air - conditioning instruments starting up was analyzed and testified through start- up experiments under various out- door temperature.